Anti-Predation Responses to Conspecific versus Heterospecific Alarm Calls by the Nestlings of Two Sympatric Birds - Yuxin Jiang; Jingru Han; Canchao Yang (Animals, 2022)
Predation is generally the main cause of bird mortality. Birds can use acoustic signals to increase their predation survival. Bird response to mobbing alarm calls is a form of anti-predation behavior. We used a playback technique and acoustic analysis to study the function of mobbing alarm calls in the parent–offspring communication of two sympatric birds, the vinous throated parrotbill (Sinosuthora webbianus) and oriental reed warbler (Acrocephalus orientalis). The chicks of these two species responded to conspecific and heterospecific mobbing alarm calls by suppressing their begging behavior. The mobbing alarm calls in these two species were similar. Mobbing alarm calls play an important role in parent–offspring communication, and chicks can eavesdrop on heterospecific alarm calls to increase their own survival. Eavesdropping behavior and the similarity of alarm call acoustics suggest that the evolution of alarm calls is conservative and favors sympatric birds that have coevolved to use the same calls to reduce predation risk.